2009
DOI: 10.1016/j.bse.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Chemical markers in Veronica sect. Hebe. III

Abstract: In a continued chemosystematic investigation of the water-soluble compounds in Veronica sect. Hebe, we have investigated two more of the species formerly classified as Parahebe. Both species contained mannitol in considerable amounts and in addition some glucosides of iridoid acids. Veronica cheesemanii was characterised by aucubin and its esters: 2′-O-benzoylaucubin and an aucubin diester named cheesemanioside. The main iridoid compounds in Veronica hookeriana were catalpol and its ester verminoside, but this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
2
13
1
Order By: Relevance
“…The HRESI MS analysis of 4 indicated a peak at m/z 409.1107 ([M+Na] + ), assigned to the molecular formula of C 17 H 22 O 10 Na. The NMR spectral analysis suggested a molecular structure which was similar to a reported glycerol α-D-glucuronide carboxylic acid (Cai et al, 2011) and its ester 9 (Maggi et. al, 2009 C-NMR spectral analysis indicated a singlet peak at δ 3.46 and δ 60.8 ppm,…”
Section: Resultssupporting
confidence: 79%
“…The HRESI MS analysis of 4 indicated a peak at m/z 409.1107 ([M+Na] + ), assigned to the molecular formula of C 17 H 22 O 10 Na. The NMR spectral analysis suggested a molecular structure which was similar to a reported glycerol α-D-glucuronide carboxylic acid (Cai et al, 2011) and its ester 9 (Maggi et. al, 2009 C-NMR spectral analysis indicated a singlet peak at δ 3.46 and δ 60.8 ppm,…”
Section: Resultssupporting
confidence: 79%
“…The 1 H-and 13 C-NMR spectral data (Table 1) suggested that 1 was a similar compound to that (9) isolated from Veronica species [13] (Fig. 1).…”
Section: Resultsmentioning
confidence: 83%
“…The residue was dissolved in 0.1 ml of dry pyridine and 0.5 mg of L-cysteine methyl ester was then added. To this mixture, 1.4 mg of o-tolylthioisocyanate in 70 ll of pyridine was added, followed by standing at 60°C for 1 h. The reaction mixture was analyzed by HPLC [ODS: Cosmosil 5C18ARII (4.6 mm 9 250 mm), CH 3 CN-50 mM H 3 PO 4 (1:3), 0.8 ml/min, UV detector at 250 nm] to give a peak for a thiocarbamoylthiazolidine derivative of D-glucuronic acid at 18.1 min [13]. The peak was identified by co-chromatography with that of authentic D-glucuronic acid (cf.…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…Labiatoides (Jensen et al, 2008). This was followed by material collected in the wild in New Zealand (Maggi et al, 2009;Taskova et al, 2010;2013). We have now investigated Veronica hookeri (Buchanan)…”
Section: Tribementioning
confidence: 99%